A framework to choose alternative analysis and selection methods. (2016) - Holzgrefe, James P.L.; Hester, Patrick T.
This paper presents a framework to investigate and choose alternative analysis and selection methods based upon a problem and its context. The research began as an investigation into the alternative analysis and selection methods used in national security planning. Existing methods were inconsistent and most violated the decision science body of knowledge. Additionally, there were no tools for planners to match an appropriate method to their problem and its context. These challenges led the researchers to develop a framework that extends beyond the technical dimension considered by legacy decision-making method selection tools by incorporating the human dimension of decision making. The developed framework also considers the sociotechnical interdependencies that occur between methods, decision analysts, and managers. A scalable, collaborative, online tool operationalises the framework for practitioners and decision makers.